Pressure dependence of vibrational optical activity of model biomolecules. A computational study - Plamitzer, Luboš; Bouř, Petr (Chirality, 2020)
Change of molecular properties with pressure is an attracting means to regulate molecular reactivity or biological activity. However, the effect is usually small and so far explored rather scarcely. To obtain a deeper insight and estimate the sensitivity of vibrational optical activity spectra to pressure-induced conformational changes, we investigate small model molecules. The Ala-Ala dipeptide, isomaltose disaccharide and adenine-uracil dinucleotide were chosen to represent three different biomolecular classes. The pressure effects were modeled by molecular dynamics and density functional theory simulations. The dinucleotide was found to be the most sensitive to the pressure, whereas for the disaccharide the smallest changes are predicted. Pressure-induced relative intensity changes in vibrational circular dichroism and Raman optical activity spectra are predicted to be 2-3-times larger than for non-polarized IR and Raman techniques.
Keywords: Disaccharides; Molecular Dynamics Simulation; high pressure; vibrational optical activity; molekulární konformace; nukleotidy; vibrace; disacharidy; dipeptidy; tlak; Optical Phenomena; simulace molekulární dynamiky; Dipeptides; optické jevy; Molecular Conformation; Vibration; Nucleotides; density functional theory; spectra simulations; molecular dynamics; Pressure